A versatile interferometric technique for probing the thermophysical properties of complex fluids - Gopal Verma; Gyanendra Yadav; Chaudry Sajed Saraj; Longnan Li; Nenad Miljkovic; Jean Pierre Delville; Wei Li (Light: Science & Applications, 2022)
Abstract Laser-induced thermocapillary deformation of liquid surfaces has emerged as a promising tool to precisely characterize the thermophysical properties of pure fluids. However, challenges arise for nanofluid (NF) and soft bio-fluid systems where the direct interaction of the laser generates an intriguing interplay between heating, momentum, and scattering forces which can even damage soft biofluids. Here, we report a versatile, pump-probe-based, rapid, and non-contact interferometric technique that resolves interface dynamics of complex fluids with the precision of ~1 nm in thick-film and 150 pm in thin-film regimes below the thermal limit without the use of lock-in or modulated beams. We characterize the thermophysical properties of complex NF in three exclusively different types of configurations. First, when the NF is heated from the bottom through an opaque substrate, we demonstrate that our methodology permits the measurement of thermophysical properties (viscosity, surface tension, and diffusivity) of complex NF and biofluids. Second, in a top illumination configuration, we show a precise characterization of NF by quantitively isolating the competing forces, taking advantage of the different time scales of these forces. Third, we show the measurement of NF confined in a metal cavity, in which the transient thermoelastic deformation of the metal surface provides the properties of the NF as well as thermo-mechanical properties of the metal. Our results reveal how the dissipative nature of the heatwave allows us to investigate thick-film dynamics in the thin-film regime, thereby suggesting a general approach for precision measurements of complex NFs, biofluids, and optofluidic devices.